1982
DOI: 10.1126/science.7089534
|View full text |Cite
|
Sign up to set email alerts
|

Fluorides and the Changing Prevalence of Dental Caries

Abstract: Community water fluoridation and individual use of fluorides have brought about a marked reduction in the prevalence of dental caries in the United States during the past 35 years. There is evidence that the prevalence of caries is declining in communities with unfluoridated water as well as in those with fluoridated water. This phenomenon may be related to an increase of fluoride in the food chain, especially from the use of fluoridated water in food processing, increased use of infant formulas with measurabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
1

Year Published

1985
1985
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(69 citation statements)
references
References 41 publications
0
68
0
1
Order By: Relevance
“…This large decline has been found in both nonfluoridated and fluoridated communities and is probably due to several factors, including the increased prevalence of fluorides "in the food chain, especially from the use of fluoridated water in food processing, increased use of infant formulas with measurable fluoride content, and even unintentional ingestion of fluoride dentifrices." 29 The study's cross-sectional data also suggest there has been a significant decline in decay level. ' ceived; and 3) if non-program preventive care had a significant impact, we would not have been able to detect the large sealant effect that was obtained.…”
Section: Discussionmentioning
confidence: 87%
“…This large decline has been found in both nonfluoridated and fluoridated communities and is probably due to several factors, including the increased prevalence of fluorides "in the food chain, especially from the use of fluoridated water in food processing, increased use of infant formulas with measurable fluoride content, and even unintentional ingestion of fluoride dentifrices." 29 The study's cross-sectional data also suggest there has been a significant decline in decay level. ' ceived; and 3) if non-program preventive care had a significant impact, we would not have been able to detect the large sealant effect that was obtained.…”
Section: Discussionmentioning
confidence: 87%
“…Similar results were obtained by other workers (Adair and Wei,1978;Tinanoff and Mueller,1978) who showed that infants being fed commercial formulae at that time may have been receiving fluoride in excess of recommended optimal dosages. Leverett (1982) suggested that it was this increase of fluoride in the food chain that had caused a slight increase in the prevalence of dental fluorosis in children living in optimally fluoridated areas. Singer and Ophaug, (1979) determined the total dietary fluoride intake of infants by analysing market-basket food collections.…”
Section: 3 Ingestion Of Fluoride From Foods and Beveragesmentioning
confidence: 99%
“…l, [12][13][14][15] The increased availability of fluorides in food has also been suggested. '3"112' Singer and his co-workers have indicated that the average daily fluoride intake for infants, two-year-olds, and young male adults is within the accepted range of 0.05 to 0.07 milligram per kilogram body weight and has not significantly changed over the past 30 years.…”
Section: Introductionmentioning
confidence: 99%